Whole MYBPC3 NGS sequencing as a molecular strategy to improve the efficiency of molecular diagnosis of patients with hypertrophic cardiomyopathy. Issue 2 (15th November 2019) - Janin, Alexandre; Chanavat, Valérie; Rollat‐Farnier, Pierre‐Antoine; Bardel, Claire; Nguyen, Karine; Chevalier, Philippe; Eicher, Jean‐Christophe; Faivre, Laurence; Piard, Juliette; Albert, Emma; Nony, Severine; Millat, Gilles
Abstract: Hypertrophic cardiomyopathy (HCM) is the most common heritable cardiomyopathy, historically believed to affect 1 of 500 people. MYBPC3 pathogenic variations are the most frequent cause of familial HCM and more than 90% of them introduce a premature termination codon. The current study aims to determine the prevalence of deep intronic MYBPC3 pathogenic variations that could lead to splice mutations. To improve molecular diagnosis, a next‐generation sequencing (NGS) workflow based on whole MYBPC3 sequencing of a cohort of 93 HCM patients, for whom no putatively causative point mutations were identified after NGS sequencing of a panel of 48 cardiomyopathy‐causing genes, was performed. Our approach led us to reconsider the molecular diagnosis of six patients of the cohort (6.5%). These HCM probands were carriers of either a new large MYBPC3 rearrangement or splice intronic variations (five cases). Four pathogenic intronic variations, including three novel ones, were detected. Among them, the prevalence of one of them (NM_000256.3:c.1927+ 600 C>T) was estimated at about 0.35% by the screening of 1, 040 unrelated HCM individuals. This study suggests that deep MYBPC3 splice mutations account for a significant proportion of HCM cases (6.5% of this cohort). Consequently, NGS sequencing of MYBPC3 intronic sequences have to be performed systematically.